2010
DOI: 10.1111/j.1365-2214.2009.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening injured children for physical abuse or neglect in emergency departments: a systematic review

Abstract: There was no evidence that any of the markers (infancy, type of injury, repeated attendance) were sufficiently accurate (i.e. LR >or= 10) to screen injured children in the ED to identify those requiring paediatric assessment for possible physical abuse or neglect. Clinicians should be aware that among injured children at ED a high proportion of abused children will present without these characteristics and a high proportion of non-abused children will present with them. Information about age, injury type and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 30 publications
(52 reference statements)
2
36
0
Order By: Relevance
“…The positive predictive values of the different individual items on screening checklists for child maltreatment have been poorly studied 11 20 21. Woodman et al 11 reviewed the evidence for the association between several characteristics and physical child abuse in injured children at the emergency department.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The positive predictive values of the different individual items on screening checklists for child maltreatment have been poorly studied 11 20 21. Woodman et al 11 reviewed the evidence for the association between several characteristics and physical child abuse in injured children at the emergency department.…”
Section: Resultsmentioning
confidence: 99%
“…Woodman et al 11 reviewed the evidence for the association between several characteristics and physical child abuse in injured children at the emergency department. They concluded that none of the characteristics (age, repeat (prior) attendance and type of injury) were accurate enough to detect child maltreatment 11. There were insufficient studies to review any other items such as severity of injury, delay in attendance and inconsistent history 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Although observational studies suggest that these may be useful, none have been shown to be sufficiently accurate or reproducible. [22][23][24][25] A brief introspection of whether the child is being abused is often enough of a consideration, but there are several chief complaints that deserve further investigation. There are "Six B's" that have high potentials for abuse and should heighten ED suspicion: bruises, breaks, bonks (head injury), burns, bites, and baby blues (Box 2).…”
Section: High-risk Chief Complaintsmentioning
confidence: 98%
“…The detection of child maltreatment depends on clinicians' ability to recognize and diagnose suspicious lesions, conduct a complete physical examination, with judicious use of diagnostic exams, and consider whether the explanation given by caregivers is supported by the characteristics of the injury or injuries and developmental capabilities of the child [10,11]. It should also be taken into account how often the child is observed by trauma [12].…”
Section: Introductionmentioning
confidence: 99%